The Digestive Fistulosis in Colonic Cancer - Schneeberger, Federico; Aliano, Artigas; Armand Ugon, Alfredo; Lorenzelli, Juan (Cirugía del Uruguay, 1980)
This paper deals with 6 cases of advanced carcinoma of the colon complicated with colo - digestive internar fistula. A reiriew of this pathology is made and documents are added. Its rare frequency the inportance of radiology for diagnosis and the poor prog,_osis in this advanced stage of the disease, is pointed out.